Khamlāṃ pāwārī ahuirona : Maitai maẏektā irambadagī haujikkī maẏektā handokacabā - Oināma Purṇaśyāma (M. Gauracandra, 1977)
On the creation myth of the deity Khamlamba and the Manipuri conduct of life.